The Role of Social Support on Self-compassionof Dormitory Students at the Muhammadiyah University of Banjarmasin - Fadilah, Inayah; Rifandi, Akhmad; Setyawati, Dyta (Jurnal Ilmiah Psikomuda (JIPM) Connectedness, 2023)
Transition period of students who live far from parents is difficult to cope with negative emotions and self-blame. The problem has an impact on blaming others, excessive self-pressure so that self-compassion is needed to overcome the problem. Social support can help students to have self-compassion. This study aims to determine the role of social support for self-compassion of Dormitory students in University of Muhammadiyah Banjarmasin. The method used is a quantitative approach with a correlational design. The sample in this study is 170 dormitory students of the University of Muhammadiyah Banjarmasin with total sampling techniques. The data collection tool of this study used a social support scale and a self-compassion scale. The type of data analysis used in this study was simple linear regression. The results of this study showed that the calculated t value was 2,032 with a significance of 0.044 < 0.05, which means that social support plays a role in self-compassion in dormitory students. Based on these results, the research hypothesis is accepted, namely that there is a role of social support for the self-compassion of dormitory students in University of Muhammadiyah Banjarmasin